Enhancing Nutritional Contents of Lentinus sajor-caju Using Residual Biogas Slurry Waste of Detoxified Mahua Cake Mixed with Wheat Straw - Gupta, Aditi; Sharma, Satyawati; Kumar, Ashwani; Alam, Pravej; Ahmad, Parvaiz (Frontiers in Microbiology, 2016)
Residual biogas slurries (BGS) of detoxified mahua cake (DMC) and cow dung (CD) were used as supplements to enhance the yield and nutritional quality of Lentinus sajor-caju on wheat straw (WS). Supplementation with 20% BGS gave a maximum yield of 1155 gkg-1 fruit bodies, furnishing an increase of 95.1% over WS control. Significant increase (p≤0.05) in protein content (29.6-38.9%), sugars (29.1-32.3%) and minerals (N, P, K, Fe, Zn) was observed in the fruit bodies. Principle component analysis (PCA) was performed to see the pattern of correlation within a set of observed variables and how these different variables varied in different treatments. PC1 and PC2 represented 90% of total variation in the observed variables. Moisture (%), lignin (%), celluloses (%) and C/N ratio were closely correlated in comparison to Fe, N and saponins. PCA of amino acids revealed that, PC1 and PC2 represented 74% of total variation in the data set. HPLC confirmed the absence of any saponin residues (characteristic toxins of mahua cake) in fruit bodies and mushroom spent. FTIR studies showed significant degradation of celluloses (22.2-32.4%), hemicelluloses (14.1-23.1%) and lignin (27.4-39.23%) in the spent, along with an increase in nutrition content. The study provided a simple, cost effective approach to improve the yield and nutritional quality of Lentinus sajor-caju by resourceful utilization of BGS.